A comparative analysis of Kurdish pre-service and in-service EFL teachers' beliefs about english language learning - Hama, Hawraz Qader (Asian E F L Journal Press business@asian-efl-journal.com, 2016)
Teacher beliefs, as part of their cognition, about English language learning and teaching vary. The consensus, however, in the literature is that EFL teacher beliefs have a profound impact on the way teachers teach in the classroom, learn how to teach, and perceive educational reforms (Borg, 2003; Freeman, 2002). This shows that exploring beliefs of EFL teachers is noteworthy for a better understanding of the state of English language education in specific EFL contexts. This quantitative study aims to explore the beliefs of Kurdish pre-service and in-service EFL teachers about English language learning and compare these beliefs to see whether any differences occur. Data were collected through administering Horwitz's (1988) Beliefs About Language Learning Inventory (BALLI) questionnaire to 23 Kurdish pre-service teachers of English from one of the public universities in Kurdistan region of Iraq, and 25 Kurdish in-service teachers of English from some basic schools in Qaladiza, a small town located in the same region. After the statistical analyses of the collected data, the results showed that both groups held both different and similar beliefs about English language learning. Furthermore, the reasons for holding these beliefs are explained in the discussion section of this study.
Keywords: BALLI; English as a foreign language (EFL); English language learning (ELL); Kurdistan region of Iraq; Teacher and learner beliefs